Parental Deployment, Adolescent Academic and Social–Behavioral Maladjustment, and Parental Psychological Well-being in Military Families. (January 2017) - Nicosia, Nancy; Wong, Elizabeth; Shier, Victoria; Massachi, Samira; Datar, Ashlesha
Objective: Increases in the frequency and length of military deployments have raised concerns about the well-being of military families. We examined the relationship between a military parent's deployment and (1) adolescent academic and social–behavioral maladjustment and (2) parental psychological well-being. Methods: We collected data from April 2013 through January 2014 from 1021 families of enlisted US Army personnel with children aged 12 or 13 during the Military Teenagers' Environments, Exercise, and Nutrition Study. Through online parent surveys, we collected data on deployment, adolescent academic and social–behavioral maladjustment, and parental psychological well-being. We estimated adjusted logistic and linear regression models for adolescents (all, boys, girls), military parents (all, fathers, mothers), and civilian parents. Results: Compared with no or short deployments, long deployments (>180 days in the past 3 years) were associated with significantly higher odds of decreases in adolescent academic performance (adjusted odds ratio [AOR] = 1.54), independence (AOR = 2.04), and being responsible (AOR = 1.95). These associations were also significant for boys but not for girls. Among parents, long deployments were associated with significantly higher odds of being depressed (AOR = 2.58), even when controlling for adolescent maladjustment (AOR = 2.54). These associations did not differ significantly between military and civilian parents and were significant for military fathers but not military mothers. Recent deployment (in the past 12 months) was not associated with either adolescent or parent outcomes. Conclusion: Long deployments are associated with adolescents' academic and social–behavioral maladjustments and diminished parental well-being, especially among boys and military fathers.